The Contextual Relationship of Surah Al-Insyirah in Ad-Dhuha: A Study of the Contextual Relationship Between Surahs - Salsabila, Aisha; Ghianovan, Jaka; Mualim, Mohamad; Fawaz, Muhammad Rashief (ZAD Al-Mufassirin, 2025)
Surah ad-Dhuha and Al-Inshirah exhibit a thematic harmony in conveying the divine blessings bestowed by Allah upon the Prophet Muhammad. The contextual relationship (munāsabah) is essential for understanding the thematic structure and the cohesive message of the Qur'an as a whole. This paper aims to explore the concept of munāsabah and the correlation between Surah ad-Dhuha and Al-Inshirah. The study adopts a qualitative approach, employing library research as the primary method of data collection. The sources include classical and contemporary tafsir works, in addition to relevant books, articles, and other academic references. Unlike previous studies, this paper analyzes the relationship between the two surahs through the lens of munāsabah theory, which has not been widely applied in this particular context. The study reveals that Surah Al-Inshirah is closely interconnected with Surah ad-Dhuha. Therefore, munāsabah enables the reader to understand how the thematic and rhetorical unity between surahs reflects the Qur’an’s deliberate structure, guiding interpretation beyond the individual verses or historical contexts.